Persuasive Strategies in American Electoral Advertisements - CHerrad, Safia; Doudi, sara (جامعة الوادي - University of Eloued, 2023)
تناقش هذه الدراسة استراتيجيات الاقناع المستخدمة في الإعلانات الانتخابية الأمريكية. كما تهدف الدراسة لمعرفة أنواع أساليب الاقناع المستخدمة من قبل هيلاري كلينتون ودونالد ترامب في خطابات حملاتهما السياسية مع تسليط الضوء على التشابهات والاختلافات بينهما. لتحليل البيانات المحصلة، تتبعت هذه الدراسة نظرية أرسطو ونموذج كروك (2004) المعدل حول الإقناع باستخدام المنهج الوصفي النوعي. حيث أظهرت نتائجها أن ترامب و كلينتون استخدما عدة أنواع من الاستراتيجيات للحصول على دعم من الجمهور في تقديم خطاباتهما السياسية. استخدم كلاهما الإيثوسوالباثوسواللوغوس بدرجات مختلفة. في حين اعتمد ترامب بشكل أساسي على الباثوس لنقل رسالته المقنعة، أما كلينتون فمالت أكثر إلى استخدام الإيثوسواللوغوس في حملاتها السياسية. تنطوي استراتيجية ترامب على استدعاء الخوف والغضب لدى الشعب مستعينا بالعواطف. من ناحية أخرى، تهدف كلينتون إلى إقناع الناس بالتصويت لصالحها من خلال تقديم أدلة استعارية قائمة على مبادئ الكراهية والتطلع والثقة. على الرغم من أن كلا المرشحين يعبران عن حبهما العميق ووطنيها وولاءهما اتجاه مؤيديها إلا أنهما يحملان مواقف سياسية متضاربة في قضايا حيوية This research discusses the persuasive strategies used American electoral advertisements. It aims to discover the kinds of convincing techniques utilized by Hillary Clinton and Donald Trump in their political campaign speeches and to highlight the similarities and differences between them. To analyze the obtained data, this study followed Aristotle's theory and Crook's (2004) modified model about persuasion following the descriptive qualitative method. The findings showed that the two politicians used several kinds of persuasive strategies to get support from the audience or publicandinvesttheirdata in delivering their political campaign speech. They both used ethos, pathos, and logos with different degree trump primarily relied on pathos to convey his persuasive message, while Clinton leaned more towards utilizing ethos and logos in her political campaigns. Trump approach involved invoking fear and anger in the audience, appealing to their emotions. On the other hand, Clinton aimed to persuade people to vote for her by providing rhetorical evidence based on principles of hatred, aspiration and confidence. Despite both candidate's deep love, patriotism and loyalty towards their audience, they held conflicting political positions on critical issues. The strategies allowed them to manipulate their audience and convince them to vote for the candidacy of the presidency in the United States.
Keywords: : دونالد ترامب, هيلاري كلينتون, الاعلانات الانتخابية, استراتيجيات الاقناع.; Donald Trump, Electoral advertisements, Hillary Clinton, Persuasive appeals.